Probe versus drill: A biomechanical evaluation of two different pedicle preparation techniques for pedicle screw fixation in human cadaveric osteoporotic spine. (May 2020) - Oikonomidis, Stavros; Grevenstein, David; Yagdiran, Ayla; Scheyerer, Max Joseph; Eh, Madita; Wegmann, Kilian; Eysel, Peer; Sircar, Krishnan
Abstract: Background: Aim of this biomechanical study was to investigate the anchorage of pedicle screws in osteoporotic vertebrae using two different preparation techniques (probe versus drill-assisted). Methods: Twelve thoracic vertebrae were used for the study. The right and left pedicles of the vertebra were prepared with a thoracic probe or a 3.2 mm drill bit and divided into two groups. A standard titanium (diameter: 5.5 mm, length: 45 mm) pedicle screw was then inserted. All pedicle screws were initially loaded with −25 N to +25 N in the cranio-caudal direction. The load was increased by 5 N every 500 cycles up to a maximum load of 10, 000 cycles. Loosening was defined as a displacement of the pedicle screw head of >5 mm. The two groups were compared in terms of maximum number of cycles and maximum force until loosening. Findings: The pedicle screws prepared with the thoracic probe failed on average after 3819 cycles (SD 3281) and the pedicle screws prepared with the 3.2 mm drill after 3335 cycles (SD 3477). There was no significant difference between the two preparation techniques ( P  = .797). With regard to the maximum force until loosening, there was also no significant difference between the two techniques (thoracic probe: 61 N (SD 33), 3.2 mm drill bit: 56 N (SD 34), P  = .791). Interpretation: Preparation of the pedicle screw hole either with a probe or drill bit doesn't seem to have an influence on pedicle screw loosening rates in the osteoporotic spine. Highlights: Biomechanical investigation of two pedicle screw preparation techniques in osteoporotic spine. No influence of the preparation technique on pedicle screw loosening rates. Compaction of the cancellous bone provides no benefits regarding pedicle screw anchorage.